The Price of Political Uncertainty: Theory and Evidence from the Option Market - KELLY, BRYAN; PÁSTOR, ĽUBOŠ; VERONESI, PIETRO (Journal of Finance, 2016)
ABSTRACT We empirically analyze the pricing of political uncertainty, guided by a theoretical model of government policy choice. To isolate political uncertainty, we exploit its variation around national elections and global summits. We find that political uncertainty is priced in the equity option market as predicted by theory. Options whose lives span political events tend to be more expensive. Such options provide valuable protection against the price, variance, and tail risks associated with political events. This protection is more valuable in a weaker economy and amid higher political uncertainty. The effects of political uncertainty spill over across countries.